Möglichkeiten und Perspektiven zum Einsatz der künstlichen Intelligenz in der Sportorthopädie - Oronowicz, Jakub; Ley, Christophe; Pachowsky, Milena; Seil, Romain; Tischer, Thomas (Sport-Orthopädie, Sport-Traumatologie, 2023)
In many scientific fields, the growth of knowledge is progressing extremely rapidly. However, this also requires new techniques to identify relevant data from the mass of evidence. Scientific evidence can help improve therapeutic decision-making as well as injury prevention and optimize return to sport activity. Artificial intelligence (AI) enables these processes to be significantly assisted. As these new concepts are known to very few orthopedic surgeons and sports physicians, this article will explain basic concepts of AI, clarify differences with classical statistics, and describe its potential applications in sports orthopedics.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Artificial intelligence; Machine learning; Sports medicine; Statistics